Drone services: issues in drones for location-based services from human-drone interaction to information processing. (3rd April 2019) - Alwateer, M.; Loke, S. W.; Zuchowicz, A. M.
ABSTRACT: Recently, drones (or unmanned aerial vehicles (UAVs)) are getting increasing attention and taking mobile computing to a new era. Due to the support of highly advanced technologies, soon they might be ubiquitous and networks of drones might be used in providing civilian drone services. In this paper, we provide a survey of drone services and applications, data management for drones, data services using drones, distributed computing trends fuelled by drones and a range of human-drone interaction research which is useful if drones are to regularly serve non-technical users, while highlighting the specific concerns in data management and airborne Internet-of-Things (IoT) computing infrastructure. We present concepts such as drones-as-a-service and fly-in,  fly-out computing infrastructure, and note data management and system design issues that arise in these situations. Issues of Big Data arising from such applications, optimising the configuration of airborne and ground infrastructure to provide the best QoS and QoE, situation-awareness, scalability, reliability, scheduling for efficiency, interaction with users and drones using different methods are noted.